2002
DOI: 10.1159/000067718
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Hormone Replacement Therapy Use Decreases Oxidative Protein Damage

Abstract: Objectives: The aim of this study is to evaluate oxidative protein damage (OPD) by investigating protein carbonyl (PCO) and nitrotyrosine (NT) levels, oxidative stress by total thiol (T-SH), erythrocyte glutathione (GSH) and nitric oxide (NO) levels in women receiving hormone replacement therapy (HRT). Materials and Methods: To examine the influence of oxidative stress on OPD, we studied 12 postmenopausal women who had received HRT for 6 months, and 13 postmenopausal women who did not receive HRT, as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
2
23
0
2
Order By: Relevance
“…It is well known that estrogens, with the contribution of their phenolic structure, have a clearance effect on ROS in both lipophilic and hydrophilic subcellular structures. Estrogens show this effect by breaking free radical chain reactions composed of membrane oxidation processes which lead to the inhibition of lipid and protein oxidation (Telci et al 2002;Topcuoglu et al 2009) due to these reasons male rats were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that estrogens, with the contribution of their phenolic structure, have a clearance effect on ROS in both lipophilic and hydrophilic subcellular structures. Estrogens show this effect by breaking free radical chain reactions composed of membrane oxidation processes which lead to the inhibition of lipid and protein oxidation (Telci et al 2002;Topcuoglu et al 2009) due to these reasons male rats were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This cardioprotection afforded by estrogen may be associated with a relaxing of the coronary artery (Gilligan et al 1994), a reduction in neutrophil infiltration (Delyani et al 1996), the scavenging of free radicals (Telci et al 2002), an increase in the production of nitric oxide (Node et al 1997), and (or) the inhibition of TNF-α production (Squadrito et al 1997). However, it has recently been shown that estrogen treatment for 6 weeks exerted no benefit on infarct size or ventricular dysrhythmias induced by left coronary occlusion and reperfusion in ovariectomized rats (Mcnulty et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently both types of treatment did not significantly affect systemic oxidative stress in vivo. Telci and colleagues examined the influence of HRT on OxS [130] in 12 postmenopausal women who had received HRT for 6 months, and 13 postmenopausal women who did not receive HRT, as the control group. They found that after the period of therapy, protein carbonyls (but not nitrotyrosine) decreased.…”
Section: Hrt (And/or Ert) and Oxsmentioning
confidence: 99%